New Directions in Federal Tax Policy for the 1980s (Book). - Hendrickson, Harvey S.; Moore, Micrael L. (The Accounting Review, 1985)
Abstract Reviews the book "New Directions in Federal Tax Policy for the 1980s," edited by Charls E. Walker and Mark A. Bloomfield.